2020
DOI: 10.7717/peerj.9445
|View full text |Cite
|
Sign up to set email alerts
|

Bioindicator potential of Ricinus communis to simulated rainfall containing potassium fluoride

Abstract: Background Fluoride pollution is a global problem because of its high phytotoxicity. Fluoride is released in air, water and soil through industrial processes, where it damages various plant species. Ricinus communis is widely distributed in Brazil, India and China and has been extensively used as a phytoremediation species in heavy metal-contaminated soils. However, few studies regarding the effect of air pollutants on R. commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…This thesis was also confirmed in other studies [69]. Riccinus communis is tolerant to a concentration of 1.5 and 3.0 mg KF•dm −3 , visual signs of toxicity such as chlorosis and necrosis and changes in parenchyma tissues, cell collapse and phenolic compound at 4.5 mg KF•dm −3 [70].…”
Section: Visual Signs Of Fluoride Phytotoxicity In Plantssupporting
confidence: 80%
“…This thesis was also confirmed in other studies [69]. Riccinus communis is tolerant to a concentration of 1.5 and 3.0 mg KF•dm −3 , visual signs of toxicity such as chlorosis and necrosis and changes in parenchyma tissues, cell collapse and phenolic compound at 4.5 mg KF•dm −3 [70].…”
Section: Visual Signs Of Fluoride Phytotoxicity In Plantssupporting
confidence: 80%
“…For the co-occurrence map (Figure 2A), studies grouped in the green cluster show that when investigating tolerant and accumulator species of a contaminant, it is important to evaluate how it enters the plant, how it behaves in the plant tissue. Furthermore, the effects fluoride presence causes on plants, whether morphological, anatomical or enzymatic, in which organs it is accumulated, how the plant reacts to the stress it causes, and if the plant eliminates it, how it does so, are also critical points to assess (Sinha et al, 2000;Saini et al, 2012;Saini et al, 2013;Singh and Verma, 2013;Koblar et al, 2015;Zhao et al, 2015;Karmakar et al, 2016;Karmakar et al, 2018;Rodrigues et al, 2020;Siahouei et al, 2020;Zhang and Chen, 2020;Calabrese and Agathokleous, 2021;Khandare et al, 2021). Plant species who show a high rate of assimilation of a given contaminant without suffering severe damage are considered accumulator species, and are ideal for the phytoremediation of that contaminant (Khandare et al, 2017;Gadi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The test is very smooth, thin and brittle. [11,12] HABITAT This plant is most common and quite wild in the jungles in India and it is cultivated throughout India, chiefly in the Tamilnadu, Bengal and Maharashtra. Two varieties of this plant are known.…”
Section: Morphologymentioning
confidence: 99%
“…[14] PHYTOCHEMICAL CONSTITUENTS Based on the Preliminary Phytochemical study of R. communis presence of steroids, saponins, alkaloids, flavonoids, and glycosides these chemical constituents are responsible for the various pharmacological actions. [12] The dried leaves of R. communis showed the presence of alkaloids, ricinine (0.55%) and N-demethylricinine flavones glycosides kaempferol-3-O kaempferol-3-O-β-D-glucopyranoside, quercetin xylopyranoside, quercetin-3-O-β-Dglucopyranoside, kaempferol O-β-rutinoside and quercetin-3-O-β-monoterpenoids (1, 8cineole, camphor and α sesquiterpenoid (βcaryophyllene), [12] gallic acid, quercetin, gentisic acid, rutin, epicatechin and ellagic acid are the major phenolic compounds isolated from leaves. Indole-3-acetic acid has been extracted from the roots The GLC study of castor oil showed the presence form of palmitic (1.2%), stearic (0.7%), arachidic (0.3 hexadecenoic (0.2%), oleic (3.2%), linoleic (3.4%), ricinoleic (89.4%).…”
Section: Benefits Of the Plantmentioning
confidence: 99%